Design Of Wedding Jewelry Stacking Mechanism With Vina Musical Instrument Theme On Kendalisodo Temple Relief - Wyna Herdiana; Prayogo Widyastoto Waluyo; Timothy Lombardi; Maria Nadya (Institut Seni Indonesia Denpasar, 2021)
Kendalisada temple dates from the middle of the 15th century which is the last stage of the Majapahit period. The author would like to re-introduce the existence of Kendalisada Temple to modern society today by designing a wedding jewelry set product inspired by the reliefs of Kendalisada Temple which tells the story of Prince Panji and Dewi Sekartaji who are sitting intimately, then the prince plays the Vina musical instrument to entertain his lover, where for the surroundings there are natural landscapes such as mountains and water. In the design process, the author used a qualitative method in the form of a literature study which includes searching for data through books, electronic sources, and related journals about Kendalisada Temple, Kendalisada Temple reliefs, Vina musical instruments, types of jewelry, jewelry materials, wedding jewelry, jewelry making techniques, markets. research, and trend forecasting. The author also used the cultural design method to transfer the culture in the relief into a product. The design process used 4 stages, namely investigation, interaction, script development, and product design. After that, the author made some ornaments and then developed more. The author uses the stacking method in jewelry making where the use of jewelry in the form of sets is stacked with a total of 2-3 pcs for each type of jewelry.